19‐4: Stereoscopic Hologram Calculation based on Gerchberg‐Saxton (GS) Algorithm. Issue 1 (May 2016) - Xia, Xinyi; Xia, Jun; Zhang, Yuning
Abstract : We propose a phase‐only CGH calculation method for stereoscopic holography. 2‐D perspective projection views of the 3‐D object are firstly generated. Based on these views, phaseonly hologram for hogel is calculated by using GS iterative algorithm instead of non‐iterative algorithm in conventional stereoscopic holography. Both simulation and optical experiment results demonstrate that our proposed method can perform higher quality reconstruction comparing with the traditional method.